PENERAPAN MODEL PEMBELAJARAN KOOPERATIF SCRAMBLE UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI MA DAR EL HIKMAH: (Implementation of Cooperative Learning Scramble Model to Improve Students’ Learning Outcome on the Subject of Colloids in Grade XI MA Dar El Hikmah) - Rahmi Khairatul Hisan; Nofri Yuhelman; Abdullah Abdullah; Elva Yasmi Amran (Perspektif Pendidikan dan Keguruan, 2017)
Research on the implementation of cooperative learning Scramble model has been done to improve student achievement on the subject of colloids in grade XI MA Dar El Hikmah Pekanbaru. The shape of this research is experimental research with pretest-posttest design. Time data collection starts in April-May 2012. The sample consists of two classes, namely the class as a class experiment XI.1 and XI.2 class as a class randomly selected control after homogeneity test. Experimental class is a class that is treated by applying the model of cooperative pembelajran Scramble. Data analysis technique used is the t-test. Based on the results of the final data processing using t-test formula obtained t count> t-table is 3.02> 1.67 means that the implementation of cooperative learning model Scramble can improve student achievement on the subject of colloids in class XI MA Dar El Hikmah Pekanbaru , Improved learning achievement in experimental class is supported with a score gain normalized (N-Gain) of 0.71 is high.